Multimodal Contrast Agents for Optoacoustic Brain Imaging in Small Animals - Shi, Xue-feng; Ji, Bin; Kong, Yanyan; Guan, Yihui; Ni, Ruiqing (Frontiers in Bioengineering and Biotechnology, 2021)
Optoacoustic (photoacoustic) imaging has demonstrated versatile applications in biomedical research, visualizing the disease pathophysiology and monitoring treatment effect in animal model, as well as towards applications in clinical setting. Given the complex disease mechanism, multi-modal imaging provide important etiological insights with different molecular, structural and functional readouts in vivo. Various multi-modal optoacoustic molecular imaging approaches have been applied in preclinical brain imaging studies, including optoacoustic/fluorescence imaging, optoacoustic imaging /magnetic resonance imaging (MRI), optoacoustic imaging /MRI/Raman, optoacoustic imaging /positron emission tomography, and optoacoustic/computed tomography, etc. There is a rapid development in molecular imaging contrast agents employing a multi-modal imaging strategy for pathological targets involved in brain diseases. Many chemical dyes for optoacoustic imaging have fluorescence properties and have been applied in hybrid optoacoustic /fluorescence imaging. Nanoparticle are widely used as hybrid contrast agents for their capability to incorporate different imaging components, tunable spectrum and photostability. In this review, we summarize contrast agents including chemical dyes and nanoparticles applied in multi-modal optoacoustic brain imaging integrating with other modalities in small animals, and provide outlook for further research.